ZIKV: Epidemiology, infection mechanism and current therapeutics - Dahiya, Nisha; Yadav, Mahima; Singh, Hitesh; Jakhar, Renu; Sehrawat, Neelam (Frontiers in Tropical Diseases, 2023)
The Zika virus (ZIKV) is a vector-borne flavivirus that has been detected in 87 countries worldwide. Outbreaks of ZIKV infection have been reported from various places around the world and the disease has been declared a public health emergency of international concern. ZIKV has two modes of transmission: vector and non-vector. The ability of ZIKV to vertically transmit in its competent vectors, such as Aedes aegypti and Aedes albopictus, helps it to cope with adverse conditions, and this could be the reason for the major outbreaks that occur from time to time. ZIKV outbreaks are a global threat and, therefore, there is a need for safe and effective drugs and vaccines to fight the virus. In more than 80% of cases, ZIKV infection is asymptomatic and leads to complications, such as microcephaly in newborns and Guillain–Barré syndrome (GBS) in adults. Drugs such as sofosbuvir, chloroquine, and suramin have been found to be effective against ZIKV infections, but further evaluation of their safety in pregnant women is needed. Although temoporfin can be given to pregnant women, it needs to be tested further for side effects. Many vaccine types based on protein, vector, DNA, and mRNA have been formulated. Some vaccines, such as mRNA-1325 and VRC-ZKADNA090-00-VP, have reached Phase II clinical trials. Some new techniques should be used for formulating and testing the efficacy of vaccines. Although there have been no recent outbreaks of ZIKV infection, several studies have shown continuous circulation of ZIKV in mosquito vectors, and there is a risk of re-emergence of ZIKV in the near future. Therefore, vaccines and drugs for ZIKV should be tested further, and safe and effective therapeutic techniques should be licensed for use during outbreaks.